Ebstein anomaly and Trisomy 21: A rare association - Stephanie L Siehr; Rajesh Punn; James R Priest; Alexander Lowenthal (Wolters Kluwer Medknow Publications, 2014)
This is a case report of a patient with Trisomy 21 with Ebstein anomaly, a ventricular septal defect, and acquired pulmonary vein stenosis; a rare combination, diagnosed during a routine neonatal examination.